Efficient Calculation of the Lattice Thermal Conductivity by Atomistic Simulations with Ab Initio Accuracy. Issue 2 (27th November 2021) - Brorsson, Joakim; Hashemi, Arsalan; Fan, Zheyong; Fransson, Erik; Eriksson, Fredrik; Ala‐Nissila, Tapio; Krasheninnikov, Arkady V.; Komsa, Hannu‐Pekka; Erhart, Paul
Abstract: High‐order force constant expansions can provide accurate representations of the potential energy surface relevant to vibrational motion. They can be efficiently parametrized using quantum mechanical calculations and subsequently sampled at a fraction of the cost of the underlying reference calculations. Here, force constant expansions are combined via the hiphive package with GPU‐accelerated molecular dynamics simulations via the GPUMD package to obtain an accurate, transferable, and efficient approach for sampling the dynamical properties of materials. The performance of this methodology is demonstrated by applying it both to materials with very low thermal conductivity (Ba8 Ga16 Ge30, SnSe) and a material with a relatively high lattice thermal conductivity (monolayer‐MoS2 ). These cases cover both situations with weak (monolayer‐MoS2, SnSe) and strong (Ba8 Ga16 Ge30 ) pho renormalization. The simulations also enable to access complementary information such as the spectral thermal conductivity, which allows to discriminate the contribution by different phonon modes while accounting for scattering to all orders. The software packages described here are made available to the scientific community as free and open‐source software in order to encourage the more widespread use of these techniques as well as their evolution through continuous and collaborative development. Abstract : Force constant potentials provided via the hiphive package are combined with GPU‐accelerated molecular dynamics simulations via the GPUMD package to obtain an accurate, transferable, and highly efficient approach for sampling the dynamic properties of materials in general and the lattice thermal conductivity in particular.